Relationship between of people's satisfaction of watershed management operations and level of their participation - Golrang, Bahram Mohammadi; Lai, Food See; Mohammad, Rostami; Mohd Noor, Khamurudin; Abd. Kudus, Kamziah; Mojgan, Mashayekhi (IDOSI Publications, 2012)
Recent studies in many countries had display the influence of many factors including: Satisfaction, Knowledge, Demographic and Attitudinal variables in level of people participation. The main question here is, whether these factors would also be effective on people participation in Iran? The purpose of this research was to investigate communication factors influencing satisfaction of farmers’ application of Watershed Management Operations (WMO) in the Kushk-Abad watershed in Khorassan Razavi Province of Iran (85km2). The general objective of this study is to assess factors that influence people’s participation in Iran. The study consist of all farmers in watershed study (N = 1500), of which 200 is selected through proportionate stratified random sampling technique (n = 200). The study was a descriptive-co relational, survey research. In fact, this research was designed to assess relationship between satisfaction of prior Watershed Management Operations (WMO) and the level of participation in WMO in Iran. In order to obtain this aim, a cross sectional survey was applied. Data for this research collected through personal interviews from three villages in Kushk-Abad sub basin in Iran. The scale of satisfaction of prior WMO and Participation in WMO were in order 0.90 and 0.92. Findings in the study indicated that a majority of the farmers have satisfaction of prior WMO. The results revealed that the level of the participation of WMO is moderate and there is a significant and positive correlation between farmers’ satisfaction of prior watershed management operations. However based on the findings, the level of economical participation of people are the more than social and environmental participation. Moreover, the results indicated that the level of the respondents’ satisfaction of prior WMO is moderate to high. This study also proved that participation in WMO is positively and significantly correlated with satisfaction of prior WMO (r = 0.584, p = 0.000).